Answer:
Hence, the function representing in the graph is:
![F(x)=4^(x+3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wb7hs1f6mmkbnov98wv9b8qkqteeoi9snl.png)
Explanation:
Clearly after looking at the given graph of a function we could observe that:
when x= -3 the function takes the value as F(-3)=1
Hence, we will check in each of the options:
A)
![F(x)=4^x](https://img.qammunity.org/2019/formulas/mathematics/middle-school/v8sf963hzqlcvxi8psrcvwb5yzlhccfe7f.png)
when x= -3 we have:
![F(3)=4^(-3)=(1)/(4^3)=(1)/(64)\\eq 1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/ti812k1eux3xdf1oh7txkegxe0p3ju6j4r.png)
Hence, option: 1 is incorrect.
B)
![F(x)=4^x-3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wrzzjk73rsb2bhrtj9ysygsury96csef65.png)
when x= -3 , we get:
![F(-3)=4^(-3)-3\\\\F(-3)=(1)/(64)-3\\eq 1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/seb1knyevjlpk836ezg0kmj7smkhfnth24.png)
Hence, option: B is incorrect.
C)
![F(x)=4^x+3](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zwcxarji6tp4npgbriz9s6in6tlbz1nw6u.png)
when x= -3 , we get:
![F(-3)=4^(-3)+3\\\\F(-3)=(1)/(64)+3\\eq 1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/zh15wloap6pk2mntdnsepopy39sj799xd9.png)
Hence, option: C is incorrect.
D)
![F(x)=4^(x+3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/wb7hs1f6mmkbnov98wv9b8qkqteeoi9snl.png)
when x= -3 , we get:
![F(-3)=4^{{-3}+3}\\\\F(-3)=4^0=1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1ahsc40tklnbakr9vyczfxyagzc8rl2j1l.png)
Hence, option: D is correct.